Technologies, Applications and Assessments for Proper Sustainable Forest Operations (SFO) - Venanzi, Rachele; Schweier, Janine; Picchio, Rodolfo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focused on the "Technologies, Applications, and Assessments for Proper Sustainable Forest Operations (SFOs)". One of the main topics was to promote knowledge for future relations between forest logging, environmental protection, and management of forests in order to provide timber at reasonable costs and other ecosystem services, such as recreation and conservation as well as biodiversity. This Special Issue contains 12 original papers, some of them reporting the outcomes of long-time experiences, reviewed by international experts in forestry and forest operations engineering fields. This Special Issue aims to increase the knowledge concerning the SFOs, with practical implications at scientific and technical levels. This Special Issue collected a representative sample of the most recent papers on the subject, which come from many different countries and cover a variety of subjects, confirming the wide scope covered by the Sustainable Forest Operations topic.